Characterization and morphological development of oil palm transformed-callus on modified culture media - Yuli Setiawati; Imron Riyadi; Dini Astika Sari; Rizka Tamania Saptari; Masna Maya Sinta; Hayati Minarsih; Turhadi; Riza Arief Putranto (INDONESIAN OIL PALM RESEARCH INSTITUTE, 2024)
Genome editing through cisgenesis develops into scientific breakthroughs in accelerating oil palm breeding programs. However, one remaining problem is the low success of transformed-calli regeneration, while its scientific explanation is still underexplored. This study aimed to characterize and regenerate transformed-calli using various amino acids and antioxidants. Transformed callus that did not regenerate (un-regenerated transformed callus or UTC) after the transformation process was taken, then T-DNA integration was detected using the NPTII gene. Furthermore, the UTC was divided into four types based on morphological characteristics. The four types of UTCs were regenerated on media enriched with glutamine (for Type-1 callus), cysteine and putrescine (for Type-2 callus), and a combination of cysteine and ascorbic acid (for Type-3 and Type-4 callus). The research results obtained NPTII successfully amplified with a band size of 700bp. The results showed that on Type-1 callus, enrichment media with 10 mg L-1 L-glutamine could induce the formation of new nodular structures on UTC Type-1. On Type-2, media enriched with 5 mg L-1 L-cysteine + 20 mg L-1 putrescine increased the density of callus structures. Media enriched with 25 mg L-1 ascorbic acid + 25 mg L-1 L-cysteine could prevent the spread of brown callus on Type-3 callus, while Type-4 callus did not show any response and became dry. Our new findings will facilitate the basic research and unregenerated transformed callus and morphological callus development behavior in oil palm.